2 0 1 5 × 2 0 1 5 + 8 0 6 4 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Slight improvement: a 2 = a is not necessarily true. You should specify that a 2 = ∣ a ∣ .
Nevertheless, good work Nihar! Keep it up.
Nice idea.
√(2015 ×2015+8064)
√(2015 ×2015+4×2016)
√((2017-2)×(2017-2)+4×(2017-1))
√(2017×2017+4-2×2017+4×(2017-1))
√(2017×2017+4-2×2×2017+4×2017-4)
√(2017×2017+4-4×2017+4×2017-4)
√(2017×2017)
2017
Grab a Calculator, Work it out
Let c = the answer. Let a = 2015 and b = 8064. So, c^2 - a^2 = 8064. Factor to get (c+a) (c-a) = 8064. Substituting back we get, c = some positive number as the terms are all positive in the addition and multiplication. (c>0 + 2015) (c>0 - 2015) = 8064. c < 2015 leads to the product being negative. c = 2015 makes the product 0. Neither of these work as 8064 is positive. Thus, we know quickly that 8064 factors into a big number greater than 2015. c = 2017 works by the first few factorings, since (2017 + 2015 = 4032) (2017 - 2015= 2) = 8064.
Nihar you should have mentioned this first: (2015²+4*2016)½ ={2015²+4(2015+1)}½ Now taking 2015=a we get, ={a²+4(a+1)}½ =(a²+4a+4)½ ={(a+2)²}½ =a+2 =2015+2 =2017
√(2015 ×2015+8064) √(2015 ×2015+4×2016) √((2017-2)×(2017-2)+4×(2017-1)) √(2017×2017+4-2×2017+4×(2017-1)) √(2017×2017+4-2×2×2017+4×2017-4) √(2017×2017+4-4×2017+4×2017-4) √(2017×2017) 2017
The trick is convert the given expression into a perfect square. Looking at 2015 x 2015, lets say we have a^2. Now evaluate the given constant so that we can get 'b' and proceed with a^2 + b^2 + 2.a.b
8064 - 2x2015 = 2017 , can be written as (2015 + 2)
Ok lets get back to original expression
2015x2015 + 2(2015 + 2017) => 2015 x 2015 + 2(2015 + 2015 + 2) we have (2015 + 2) ^2 i.e. sqrt(2017^2)
Problem Loading...
Note Loading...
Set Loading...
Let 2015 = a . Now the given expression can be written as :
a 2 + 4 a + 4 = ( a + 2 ) 2 = a + 2 = 2 0 1 5 + 2 = 2 0 1 7